Implementation of Non-state Pension Provision in Ukraine in the System of Strengthening Social Protection - Cheberyako, Oksana; Varnalii, Zakharii; Нurochkina Viktoriia; Miedviedkova, Nataliia (Ekonomika, 2023)
This paper is devoted to identifying the features and finding solutions to the problems of the formation and improvement of the non-state pension provision of Ukraine in the system of strengthening social security and preventing the degradation of the social structure. It presents the results of a study of emergent dynamics of the main performance indicators of non-state pension provision in Ukraine and the behavioural aspects of its beneficiaries when choosing a financial intermediary in the implementation of a new metadata specification based on three areas: banking institutions, non-state pension funds (NPFs) and life insurance companies. These results are the following: identification of key trends in non-state pension provision in Ukraine; disclosure of problems, obstacles, and major shortcomings of an organizational and legal nature; determination of directions for solving problems and the dominant factors in the development of non-state pension provision in Ukraine.